PEMBINAAN PEGAWAI UNTUK PENINGKATKAN DISIPLIN KERJA DI DINAS PEKERJAAN UMUM KOTA PONTIANAK - E.21109063, Syarifudin (PublikA, Jurnal Ilmu Administrasi Negara, 2013)
Human resources is one important factor in the organization, because it plays a role in conducting activities to achieve goals. That's why we need a coaching for employees to improve and enhance the quality and quantity of employees. In addition, the guidance also aims to improve employee discipline. This study focuses on the implementation of the guidance to the employee coaching skills as well as intellectual and mental and spiritual development. The focus of the research discussed using qualitative methods and case study research conducted in the Dinas Pekerjaan Umum Kota Pontianak. From the results of the study found that coaching is conducted in Dinas Pekerjaan Umum Kota Pontianak is less than optimal, so there are still several irregularities committed by the employee. One deviation that occurs is of some employees still come too late. Therefore, the researchers suggested that coaching can provide intellectual leadership and skills optimally in order to improve the quality of employment. Leaders are also expected to provide mental and spiritual guidance to the employee.Keywords: Intellectual and Skills Development, Mental and Spiritual Development, Employee Work Discipline.